MENGGALI MOTIVASI GURU AGAMA KATOLIK DI SEKOLAH TINGGI PASTORAL KATEKETIK (STPK) SANTO BENEDIKTUS SORONG - Ady Bintoro (Jurnal Teologi (Journal of Theology), 2015)
A Catholic teacher, while he is open as it must be to the situation of the contemporary world, leads its students to promote efficaciously the good of the earthly city and also prepares them for service in the spread of the Kingdom of God, so that by leading an exemplary apostolic life they become as it were a saving leaven in the human community. They should therefore be very carefully prepared so that both in secular and religious knowledge they are equipped with suitable qualifications and also with a pedagogical skill that is in keeping with the findings of the contemporary world. Intimately linked in charity to one another and to their students and endowed with an apostolic spirit, may teachers by their life as much as by their instruction bear witness to Christ, the unique teacher. But then, the problems are who wants to be a Catholic teacher among the choices in the world and offer even better than a Catholic teacher? This article aims to support people especially who wants to be a Catholic.